Numbers and distribution of White-fronted and Pink-footed Geese in Flanders (Belgium), 1981-87 in a North West European context - Meire, Patrick M; Kuijken, Eckhart; Devos, Koen (Wildfowl, 1988)
This paper deals with the numbers of Whitefronts Anser albifrons and Pinkfeet A. brachyrhynchus wintering in Flanders (Belgium) during the period 1981-87. Four important wintering haunts are described. The Oostkustpolders and the Antwerp region are visited each winter by geese, whereas the Ijzervallei and NE Flanders, both discovered by the geese during the very severe winter 1978-79, are used only during severe winters. The dispersion of geese in the Oostkustpolders during the last 25 years in relation to protection measures is examined. The pattern of occurrence of both species is discussed in relation to weather conditions and the West European population distribution. Up to 86,000 Whitefronts and nearly 15,000 Pinkfeet were the maxima counted. Nearly every winter a substantial part of the Pinkfeet population is not accounted for in the counts. Keeping disturbance as low as possible is necessary to secure the value of wintering haunts for geese.